Ответ(ы) на вопрос:
[latex](x^{ \frac{1}{3} } + x^{ -\frac{1}{3} } )^2-2= \\ \\ x^{ \frac{2}{3} } +2 x^{ \frac{1}{3} } * x^{ -\frac{1}{3} } + x^{ -\frac{2}{3} }-2 \\ \\ = x^{ \frac{2}{3} } +2 x^{( \frac{1}{3} -\frac{1}{3} )} + x^{ -\frac{2}{3} }-2 = \\ \\ x^{ \frac{2}{3} } +2 x^{0} + x^{- \frac{2}{3} } -2= \\ \\ x^{ \frac{2}{3} } + x^{- \frac{2}{3} } +2-2=x^{ \frac{2}{3} } +x^{- \frac{2}{3} }\\ \\ [/latex]
[latex] (x^{ \frac{1}{3} } - x^{- \frac{1}{3} } )^2+2= x^{ \frac{2}{3} } + x^{ -\frac{2}{3} } [/latex]
[latex](1- x)^ \frac{3}{4} =(1-0.9919)^ \frac{3}{4} = \\ \\ (0.0081)^{ \frac{3}{4} } = (\sqrt[4]{0.0081})^3=(0.3)^3=0.027 [/latex]
Не нашли ответ?
Похожие вопросы